The HECT Domain of the Ubiquitin Ligase Rsp5 Contributes to Substrate Recognition - Lee, Jacqueline R. E. (American Society for Biochemistry and Molecular Biology, 2009)
Ubiquitin modification of endosomal membrane proteins is a signal for active inclusion into the Multivesicular Body (MVB) pathway, resulting in lysosomal degradation. However, the endosome represents a dynamic site of protein sorting with a majority of proteins destined for recycling, rather than MVB targeting. Substrate recognition by ubiquitin ligases is therefore highly regulated. We have investigated substrate recognition by the Nedd4 ortholog Rsp5 as a model for understanding ligase-substrate interactions. Rsp5 interacts directly with its substrate Cps1 via a novel interaction mode. Perturbation of this mode of interaction revealed a compensatory role for the Rsp5 adaptor Bsd2. These results highlight the ability of Rsp5 to interact with substrates via multiple modalities, suggesting additional mechanisms of regulating this interaction and relevant outcomes.